Olfactory stimulation for people with dementia: A rapid review. (July 2022) - D'Andrea, Federica; Tischler, Victoria; Dening, Tom; Churchill, Anne
There is a growing interest in using olfactory (smell) stimulation in dementia care. This study aims to extend current knowledge by synthesising the evidence on the efficacy of interventions using olfactory stimulation for people with dementia and to assess the effects of different types of odours and administration methods using a mixed methods approach. The rapid review was conducted based on searches in six electronic databases. A narrative approach was applied to assess 20 studies included in the review. Fourteen studies used a quasi-experimental design, five studies used an experimental design and one was a case study. High heterogeneity was found on odours and methods of application used, with the majority of studies administering lavender oil using a diffuser. Mixed results were reported on the benefits of olfactory stimulation on responsive behaviours and cognitive function. Although the evidence available is limited, encouraging results were found regarding olfactory stimulation and increased sleep duration, food intake and improved balance. It was not possible to draw any overall conclusion in relation to the effect of olfactory stimulation. However, this review shows promising results that support further investigation of olfactory stimulation as a nonpharmacological intervention for people with dementia. The review is limited due to the low to moderate quality of studies included. Furthermore, the broad range of approaches was employed, and comparison between the studies was difficult. Further high-quality mixed method studies using robust and detailed protocols are needed to clarify the effects of olfactory stimuli and any other factors that may influence the responses of people with dementia.